A morning-specific phytohormone gene expression program underlying rhythmic plant growth. - Todd P Michael; Ghislain Breton; Samuel P Hazen; Henry Priest; Todd C Mockler; Steve A Kay; Joanne Chory (PLoS Biology)
Most organisms use daily light/dark cycles as timing cues to control many essential physiological processes. In plants, growth rates of the embryonic stem (hypocotyl) are maximal at different times of day, depending on external photoperiod and the internal circadian clock. However, the interactions between light signaling, the circadian clock, and growth-promoting hormone pathways in growth control remain poorly understood. At the molecular level, such growth rhythms could be attributed to several different layers of time-specific control such as phasing of transcription, signaling, or protein abundance. To determine the transcriptional component associated with the rhythmic control of growth, we applied temporal analysis of the Arabidopsis thaliana seedling transcriptome under multiple growth conditions and mutant backgrounds using DNA microarrays. We show that a group of plant hormone-associated genes are coexpressed at the time of day when hypocotyl growth rate is maximal. This expression correlates with overrepresentation of a cis-acting element (CACATG) in phytohormone gene promoters, which is sufficient to confer the predicted diurnal and circadian expression patterns in vivo. Using circadian clock and light signaling mutants, we show that both internal coincidence of phytohormone signaling capacity and external coincidence with darkness are required to coordinate wild-type growth. From these data, we argue that the circadian clock indirectly controls growth by permissive gating of light-mediated phytohormone transcript levels to the proper time of day. This temporal integration of hormone pathways allows plants to fine tune phytohormone responses for seasonal and shade-appropriate growth regulation.